2011
DOI: 10.1101/lm.2000811
|View full text |Cite
|
Sign up to set email alerts
|

Repeatedly reactivated memories become more resistant to hippocampal damage

Abstract: We examined whether repeated reactivations of a context memory would prevent the typical amnesic effects of post-training damage to the hippocampus (HPC). Rats were given a single contextual fear-conditioning session followed by 10 reactivations, involving a brief return to the conditioning context (no shock). Subsequently, the rats received sham or complete lesions of the HPC. When tested for retention, the HPC rats that experienced the reactivations froze significantly more than nonreactivation HPC rats and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
1
18
2
Order By: Relevance
“…In contrast, we found that a less intense conditioning and more spaced reactivation protocol led to a prolonged period of hippocampus memory dependence. This discrepancy between our findings and that of Lehmann and McNamara (2011) may be due to methodological differences (lesioning vs. pharmacological inactivation) and different time intervals between reactivation and testing (3 weeks vs. 1 week). Another possibility is that massed memory reactivation soon after training may enable extra-hippocampal structures to encode the fear memory similar to multi-day overtraining, whereas a more spaced protocol, as used in our study, impedes systems consolidation and maintains the memory in a detailed, hippocampus dependent state.…”
contrasting
confidence: 81%
See 1 more Smart Citation
“…In contrast, we found that a less intense conditioning and more spaced reactivation protocol led to a prolonged period of hippocampus memory dependence. This discrepancy between our findings and that of Lehmann and McNamara (2011) may be due to methodological differences (lesioning vs. pharmacological inactivation) and different time intervals between reactivation and testing (3 weeks vs. 1 week). Another possibility is that massed memory reactivation soon after training may enable extra-hippocampal structures to encode the fear memory similar to multi-day overtraining, whereas a more spaced protocol, as used in our study, impedes systems consolidation and maintains the memory in a detailed, hippocampus dependent state.…”
contrasting
confidence: 81%
“…These studies suggest that overtraining of contextual fear discrimination allows extrahippocampal structures to encode the memory, thus shortening or avoiding a period of time that memory expression is sensitive to hippocampal manipulations. Interestingly, a recent study found that following a strong training protocol (10 shocks) and a more intense memory reactivation schedule (23 a day for 5 days), memory was rendered insensitive to hippocampal lesions when tested in the training context (Lehmann and McNamara, 2011). This study did not test the context-specificity of the memory expression.…”
mentioning
confidence: 89%
“…Some previous work has implicated medial frontal cortex in successful long-term memory. For example, medial prefrontal cortex has been implicated in systems-level consolidation of memories in humans (Takashima et al, 2007;Sterpenich et al, 2009;van Kesteren et al, 2010) and in rodents (Frankland and Bontempi, 2005;Restivo et al, 2009;Lehmann and McNamara, 2011). Also, Eriksson et al (2011) demonstrated a relationship between longterm retention after successful repeated retrieval and medial prefrontal cortex activity (in dorsal medial PFC/ACC).…”
Section: Day 1 Bold Signal Changes In Relation To Successful Longtermmentioning
confidence: 99%
“…For example, in the conditioned place preference task, amnestic treatments disrupted reconsolidation for weak memories (four pairings), but had little effect on stronger memories (eight pairings) reactivated 1 d after training (Robinson and Franklin 2010). In the fear conditioning task, an increase of training strength by increasing the number of CS -US associations makes the reactivated memory trace less susceptible to interference (Suzuki et al 2004;Lehmann and McNamara 2011). However, it has been reported that strong memories can still be destabilized and then undergo reconsolidation relatively to their age (Wang et al 2009), suggesting that boundary conditions to the reconsolidation process can be in interaction.…”
mentioning
confidence: 99%